Petroleum exploration and exploitation in Norway : proceedings of the Norwegian Petroleum Society Conference, 9-11 December 1991, Stavanger, Norway - Norsk petroleumsforening. Conference (1991 : Stavanger, Norway); Hanslien, S.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1995)
This conference was arranged by the Norwegian Petroleum Society in order to commemorate the first 25 years of exploration on the Norwegian Continental Shelf. Sixty papers and posters were presented of which 25 have been selected for this volume. Since the start of exploration activities during the mid 1960's the North Sea has not only proved to be one of the main petroleum provinces in the world, but has also established itself as an excellent laboratory for geoscientific research and application. This development has been stimulated greatly by the openess towards exchange of technical data encouragement by the Norwegian authorities. The objective of this book is to assess the results of 25 years of exploration in Norway. It focuses on lessons learned from past experiences as well as considering future challenges facing geoscientists in the industry (relating to both exploration and exploitation activities). Included, are papers which assess the status and future trends of exploration in the main geological provinces on the Norwegian Continental Shelf from the Central Graben in the south to Svalbard and the Russian Artic in the north.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Petroleum -- Norway; TECHNOLOGY & ENGINEERING -- Petroleum; Petroleum; Norway; Electronic books